East Asia and the First World War - Jacob, Frank (De Gruyter, 2022)
The First World War was a truely global event that changed the course of history in many participating as well as non-participating countries. In East Asia, the war stimulated the further rise of Japan as the leading power in the region during the war, yet also its radicalization and social protests after 1918.